FUNGICIDE PROPERTIES in Vitro OF CHITOSAN ETHYL CARBAMATE IN THE CONTROL OF VINEYARDS FUNGIES IN CHILE - Galo Cárdenas-Triviño; Luis Vergara-González; Camila Salamanca (Journal of the Chilean Chemical Society, 2019)
The grape table is the main fresh fruit export of Chile. However, is affected in the first place by fungal pathogens, resulting between 10 % and 15 % losses in production. The commercial use of biocides has a weakness generating an increase in demand for new antifungal agents. Chitosan and carbamate possess fungicidal properties;therefore the aim of this paper is to analyze the fungicidal activity of chitosan ethylcarbamate. In vitro bioassays were carried out to evaluate the effectiveness of the fungicide to control Botrytis cinerea and Fusarium spp. fungies. The chemical composition of chitosan ethylcarbamate was determined previously. The fungi growth curves and fit with the program DMfit, which uses the Baranyi model to obtain the growth parameters were studied. Then, we estimated the MIC (minimum inhibitory concentration) by a microdilution method. These data were analyzed by simple linear regression. Growth parameters of Fusarium spp shows a growth rate of 1.3 h-1, and Botrytis cinerea of 0.9 h-1, respectively. Chitosan ethylcarbamate with a MIC of 1250 mg/L on Fusarium spp. and B. cinerea a MIC of 1250 mg/L were obtained. Finally, the chitosan ethyl carbamate fungicide, biodegradable, is a more ecological alternative to the conventional fungicides such as Iprodione, Zineb, Nabam, Maneb and the traditional Bordeaux mixture.